Study on Manufacturing Grid and its executing platform. (13th March 2008) - Tao, F.; Hu, Y.F.; Zhou, Z.D.
Advanced manufacturing technologies and modes, grid technologies, information technologies and advanced management technologies were integrated to solve the resource sharing and collaborative operation in current manufacturing process. A new manufacturing mode namely Manufacturing Grid (MGrid) was presented. After the grid and its applications were summarised, the concept of MGrid was discussed firstly, and the related works about MGrid as well. Then the differences between MGrid and networked manufacturing and computational grid, the structure and main functions of MGrid system, were put forward. The executing platform of MGrid and its main workflow were presented thirdly. An application prototype, namely MBRSSP-MGrid, was developed to show the workflow of MGrid system.